The Potential of Pro-Poor Tourism (PPT) Strategies as a Vehicle for Reducing Poverty in Langkawi Island, Kedah Darul Aman - Hasrina, Hassan (2004)
Tourism activity is usually seen as a leisure activity of the rich. In most countries, where there exist potential for development of tourism product, the focus of tourism policy and strategy is usually on attracting potential tourist to visit the country. The main objective of developing tourism industries is on maximizing foreign earnings, income and employment creation. Tourism development is therefore designed without making into account the needs and opportunities of the poor to participate in the tourism industry. Thus, there are potentials for the poor to get involve and hence making tourism as one of the strategy to reduce poverty. Langkawi Island, which is situated in the state of Kedah Darul Aman, has been identified to an interesting case study for exploring the poverty impacts of tourism industry. Since Langkawi Islam has been promoted as one of he major tourist destinations to Malaysia, Kedah state policy makers should also consider the "pro-poor tourism" (PPT) idea. PPT is not a specific product or sector of tourism, but an approach to the industry. It involves government, the private sector and civil society, as well as the poor themselves who act a both producers and decision-makers. Thus, this study will investigate he potentials of PPT strategies as a vehicle in reducing poverty in Langkawi Island.